2010
DOI: 10.1177/1086026609358969
|View full text |Cite
|
Sign up to set email alerts
|

Powerful or Just Plain Power-Full? A Power Analysis of Impact and Benefit Agreements in Canada’s North

Abstract: Impact and benefit agreements (IBAs) between natural resource developers and Aboriginal communities are increasingly portrayed as viable approaches to assure Aboriginal people will reap economic benefits of resource extraction in their traditional territories. Drawing from existing literature about the social context of IBA negotiations, especially in Northern Canada, the authors’ analysis contributes to the study of negotiated agreements by using Lukes’s three dimensions of power to examine how IBAs confer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 46 publications
0
82
0
1
Order By: Relevance
“…Yet as private contacts, IBAs are not subject to the same requirements for transparency and democratic participation as EAs, which are regulated by provincial or federal environmental assessment legislation. At least one commentator has suggested that the confidentiality clauses might hurt Indigenous groups since Indigenous governments and communities have less power in negotiations than large corporations (Caine and Krogman, 2010). Confidentiality clauses are primarily included to protect financial information; however, they make it difficult to monitor the socioeconomic and environmental provisions that are also in IBAs (Fidler, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet as private contacts, IBAs are not subject to the same requirements for transparency and democratic participation as EAs, which are regulated by provincial or federal environmental assessment legislation. At least one commentator has suggested that the confidentiality clauses might hurt Indigenous groups since Indigenous governments and communities have less power in negotiations than large corporations (Caine and Krogman, 2010). Confidentiality clauses are primarily included to protect financial information; however, they make it difficult to monitor the socioeconomic and environmental provisions that are also in IBAs (Fidler, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between EAs and IBAs, however, is not well defined in the literature and is often case-specific. While some scholars have applauded IBAs as a mechanism to address weaknesses in the EA processes (Galbraith et al, 2007;O'Faircheallaigh, 2007;Noble and Fidler, 2011), others have problematized the use of IBAs as a regulatory mechanism arguing that IBA negotiations can lessen the effectiveness of EA processes and that power differences constrain the ability of communities to ensure that companies follow through on their IBA commitments (Fidler and Hitch, 2007;Caine and Krogman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…18 IBAs in Canada are mostly "privately negotiated agreements" typically formed between Indigenous communities and extractive companies. 19 They may be required in Land Claims Agreements between Indigenous peoples and the Canadian Government, 20 form part of the consultation process for extractive projects or be voluntarily negotiated. 21 It appears that IBAs in Canada are influenced by the prevailing Canadian consultation model 22 which, in its tendency to focus on consultation and attendant factors, is more akin to that of ILO Convention 169 than to a consent model following the FPIC principles enunciated in the UNDRIP.…”
Section: The Nature and Scope Of Contractsmentioning
confidence: 99%
“…They are nonetheless optimistic that technical and institutional changes-land claims agreements and impact benefit agreements (IBAs)-can improve the outcome of mining ventures. However, recent examinations of IBAs and their implementation suggest they do not necessarily contribute to critical examination of the impacts of development or even to implementation of effective mitigation measures (Caine and Krogman 2010;Czyzewski et al in press). Harvey (1996) calls this faith in technical and institutional measures "ecological modernization."…”
Section: Legitimisation and Accumulation Functions Of The Statementioning
confidence: 99%